Model Pembelajaran Pendidikan Multikultural Dalam Pelajaran IPS Di Sekolah Kreatif SD Muhammadiyah 20 Surabaya - Choirul Mahfud (TADARUS, 2014)
ABSTRACT Researching on the implementation of the Social Sciences (IPS) learning in the environment of Islamic Elementary School is interesting and need to be done, because in the current curriculum, learning of social studies tend to be conducted separately and each is as monolithic and mono-culturally. The focus of this research is to discuss what and how the model of multicultural education learning in social studies in the School of Creative 5th Grade of SD Muhammadiyah 20 Surabaya? Any factors that support and hinder the implementation of it? This qualitative descriptive study based on primary and secondary sources of in-depth interviews, and documentations. After doing thorough research on multicultural education in the teaching model of 5th grade Social Studies at the School of Creative SD Muhammadiyah 20 Surabaya, it can be concluded that: From the research done by the researcher, that the learning model of multicultural education in social studies lessons in the School of Creative Class 5 SD Muhammadiyah 20 is the result of collaborating from various multicultural approaches and humanistic approaches, including, the basic concept of edutainment, active learning, the accelerated learning, and learning quantum. With the aim to make learning more fun and exciting students. Therefore, facilitate understanding and practice in teaching and learning for both teachers and students. Several factors support in the implementation of multicultural based social sciences learning: Firstly, support from the leadership of Muhammadiyah branch Bubutan Surabaya. Knowingly or not the success of Creative School can not be separated from the head of the Muhammadiyah. Secondly, financial support. Creative School is financially quite well, thus able to finance the programs to be implemented. Thirdly, public support. Learning practices in the implementation of multicultural education in social studies lessons as a practice in villages around the school, the community support these activities. Of course without the help of all parties will not run smoothly. Key Words: Social Studies, Multicultural Education, Creative, Tolerance, Anti-Violence and Peace